Perlindungan Hukum dan Mekanisme Penyelesaian Sengketa Penanaman Modal Bagi Penanam Modal Asing di Negara Indonesia - Prasasti Dyah Nugraheni; Sang Ayu Putu Rahayu (JURNAL HUKUM PELITA, 2025)
The writing of this scientific article has various objectives, which describe the regulation of legal protection for Foreign Investors in Indonesia, a guarantee of legal certainty for Foreign Investors in Indonesia, and the dispute-resolution process between the Indonesian Government and Foreign Investors in Indonesia. The writing of this scientific article uses a type of research that is normative juridical with data collection techniques in the form of qualitative literature studies that will be studied legally and normatively following various regulations and various existing legal facts. The results of writing this scientific article, are as follows the regulation of legal protection for Foreign Investors in Indonesia is regulated in Article 6-Article 8 of Law Number 25 of The Year 2007 concerning Investment, the guarantee of legal certainty for foreign investment in Indonesia can be realized by improving and increasing the quality of infrastructure facilities, commodity facilities, democratic conditions, investment risks, and political stability in Indonesia, and the dispute-resolution process between the Indonesian Government and Foreign Investors in a foreign investment activity in Indonesia can be resolved through a process of consensus and international arbitration following the agreement between the Indonesian Government and Foreign Investors